Reading an Erased Code : Romantic Religion and Literary Aesthetics in France - Despland, Michel (Book collections on Project MUSE., 1994)
The five writers treated by Despland helped shape a broader definition of belief, on that included individual sensibility. The works they produced are, in a sense, new religious texts.